Utilizing the Enrichment Triad Model in History Learning: a Conceptual Framework (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: History learning brings students the ability to construct past events. History as the means to shape youth characteristics in understanding the nation. However, there are several identical issues found within the history learning process that relates to many factors. The enrichment Triad Model is a theoretical learning model that was initially framed for gifted students. It has been applied and tested into any level of grade and many subjects and students with average ability. The Enrichment Triad Model has several prominences that are suitable for history learning. It enhances students’ interests, curiosity, participation, and also learning outcomes. Enrichment Triad Model has three main types with varied activities to be applied upon history learning: General Exploratory Activities, General Training Activities, and Individual and Small Investigation of Real Problems. Unfortunately, many Indonesian educators and scholars have not recognized this model, referring to the scarcity of publication. Besides, several prior research was mainly conducted on the gifted program, not the regular ones. This article is a descriptive study that discussing how Enrichment Triad Model being implemented in history learning for regular programs and to solve the common issues with providing interest-based learning. There is a growing interest in research on how the Enrichment Triad Model may support the needs of pedagogical practice. Abstrak: Sejarah sebagai salah satu cara untuk membentuk karakter generasi muda dalam memahami bangsanya. Akan tetapi, ada banyak persoalan yang muncul dalam pembelajaran sejarah yang diakibatkan oleh berbagai factor. Enrichment Triad Model merupakan suatu model belajar yang adaptif yang pada awalnya diperuntukkan untuk peserta didik yang dianggap cerdas. Model ini telah diterapkan pada berbagai tingkat pendidikan dan berbagai mata pelajaran, dan juga peseta didik dengan kemampuan rata-rata. Enrichment Triad Model memiliki banyak keunggulan yang cocok untuk pembelajaran sejarah yang mampu meningkatkan ketertarikan, rasa ingin tahu, partisipasi, dan hasil belajar peserta didik. Enrichment Triad Model memiliki tiga tipe umum dengan berbagai aktivitas belajar yang dapat diterapkan dalam pembelajaran sejarah, antara lain General Exploratory Acntivities, General Training Activities, dan Individual and Small Investigation of Real Problems. Masing-masing tahap bersifat akomodatif dan fleksibel. Namun demikian, model ini tidak banyak dikenal para pendidik dan akademisi di Indonesia berdasarkan jumlah publikasi yang ada. Selain itu, penelitian yang dilakukan sebelumnya lebih banyak diterapkan untuk program kelas khusus ‘anak berbakat,’ dibandingkan kelas regular. Artikel ini merupakan deskriptif yang membahas bagaimana penerapan Enrichment Triad Model dalam pembelajaran sejarah untuk kelas regular dan mengatasi persoalan-persoalan yang lazim ditemui dengan menyediakan pembelajaran berbasis minat peserta didik. Saat ini, kajian tentang Enrichment Triad Model terus berkembang untuk mengatasi dan memenuhi kebutuhan dalam pelaksanaan pedagogis pendidikan.